1992
DOI: 10.1182/blood.v80.10.2604.2604
|View full text |Cite
|
Sign up to set email alerts
|

Hexamethylene bisacetamide in myelodysplastic syndrome and acute myelogenous leukemia: a phase II clinical trial with a differentiation- inducing agent

Abstract: Hexamethylene bisacetamide (HMBA) is a potent inducer of differentiation of a number of transformed cell lines in vitro. We report results of a phase II clinical trial in 41 patients with myelodysplastic syndrome (MDS) or acute myelogenous leukemia (AML) to whom HMBA was administered by continuous infusion for 10 days and repeated after an interval of 18 to 75 days. HMBA induced a complete remission (CR) in three patients and a partial remission (PR) in six patients. The median duration of CR was 6.8 months (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…A phase II clinical trial was conducted using HMBA to treat patients with MDS or AML. Of the 41 patients in the trial, HMBA induced a complete remission in three patients and a partial remission in six patients (60).…”
Section: Discussionmentioning
confidence: 98%
“…A phase II clinical trial was conducted using HMBA to treat patients with MDS or AML. Of the 41 patients in the trial, HMBA induced a complete remission in three patients and a partial remission in six patients (60).…”
Section: Discussionmentioning
confidence: 98%
“…The effective doses of HMBA are at low millimolar concentrations. Phase II clinical studies indicated high toxic effects, though complete or partial remission was achieved in some patients with myelodysplastic syndrome or acute myelogenous leukemia (7).…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that transformed cancer cells acquire uncontrolled growth and metastasis potential through dedifferentiation, and induction of differentiation can reverse transformation and restore growth and multiplication controls. HDAC inhibitors have been shown to induce differentiation in a wide variety of cancer cells by modulating chromatin remodeling36, 37 and transcriptional activation of genes 38. Similarly recent studies have shown that the induction of senescence can restrict tumor growth39 and cause reversal of drug resistance 40, 41, 42, 43, 44.…”
mentioning
confidence: 98%